Targeting Fibroblast Growth Factor Receptor Pathway: Precision Medicine for Biliary Cancer and Beyond - Uson Junior, Pedro Luiz Serrano; Borad, Mitesh J. (Seminars in Liver Disease, 2023)
Fibroblast growth factor receptor 2 (FGFR2) inhibitors are now being included in the treatment guidelines of multiple countries for patients with advanced cholangiocarcinoma (CCA). Activation of the FGF–FGFR pathway is related to proliferation and tumor progression. Targeting the FGF–FGFR pathway is effective and can yield durable responses in patients with CCA harboring FGFR2 fusions or rearrangements. In this review article, we address molecules and clinical trials evaluating FGFR inhibitors in advanced CCA. We will further discuss identified mechanisms of resistance and the strategies to overcome it. The incorporation of next-generation sequencing in advanced CCA and circulating tumor DNA on disease progression will unveil mechanisms of resistance and improve the development of future clinical trials and more selective drugs and combinations.
Keywords: cholangiocarcinoma; FGFR2; biliary cancers; pemigatinib; infigratinib; futibatinib